O preço dos aluguéis e o acesso à moradia em São Paulo: um estudo de caso na ocupação Vila Nova Palestina - Garcia, Marilia Gabriela Bello (2024)
The objective of this work was to study the relationship between the excessive rent burden in the city of São Paulo, from 2008 onwards, and the adoption of alternative occupation as a solution to access to housing. Articulating the analysis of the impacts of the mechanisms necessary to make housing policy viable, such as the availability of real estate credit, reclassification of social classes, minimum wage appreciation policy, among others, the investigative investigation understands how the combination of these conditions affected the price of formal rents impacting the low-income population. From 2008 onwards, with the launch of the Minha Casa Minha Vida Programme, the value of formal rentals rose rapidly in Brazilian metropolitan regions, gaining relevance in analyzes of the real estate market and impacting the housing deficit, in the excessive rental burden component. In São Paulo, the rise in the rental market can be observed on internet portals such as FipeZap and ImovelWeb, which select samples of advertisements. Given this rising situation and the difficulty for families to pay rent, the main representative of social housing movements, Guilherme Boulos, pointed out the excessive burden of rent as the main factor in families joining social housing movements. The difficulty of families paying their rent was analyzed, analytically, based on the income contained in the records of the participants of the Vila Nova Veneza Occupation made available for the analysis of this research